Animation-supported consent for urgent angiography and angioplasty: a service improvement initiative. Issue 22 (10th March 2020) - Wald, David S; Casey-Gillman, Oliver; Comer, Katrina; Mansell, Josephine Sarah; Teoh, Zhi H; Mouyis, Kyriacos; Kelham, Matthew; Chan, Fiona; Ahmet, Selda; Sayers, Max; McCaughan, Vincent; Polenio, Nito
Abstract : Objective: Patient understanding of angiography and angioplasty is often incomplete at the time of consent. Language barriers and time constraints are significant obstacles, particularly in the urgent setting. We introduced digital animations to support consent and assessed the effect on patient understanding. Methods: Multi-language animations explaining angiography and angioplasty (www.explainmyprocedure.com/heart ) were introduced at nine district hospitals for patients with acute coronary syndrome before urgent transfer to a cardiac centre for their procedure. Reported understanding of the reason for transfer, the procedure, its benefits and risks in 100 consecutive patients were recorded before introduction of the animations into practice (no animation group) and in 100 consecutive patients after their introduction (animation group). Patient understanding in the two groups was compared. Results: Following introduction, 83/100 patients reported they had watched the animation before inter-hospital transfer (3 declined and 14 were overlooked). The proportions of patients who understood the reason for transfer, the procedure, its benefits and risks in the no animation group were 58%, 38%, 25% and 7% and in the animation group, 85%, 81%, 73% and 61%, respectively. The relative improvement (ratio of proportions) was 1.5 (95% CI 1.2 to 1.8), 2.1 (1.6 to 2.8), 2.9 (2.0 to 4.2) and 8.7 (4.2 to 18.1), respectively (p<0.001 for all comparisons). Conclusion: Use of animations explaining angiography and angioplasty is feasible before urgent inter-hospital transfer and was associated with substantial improvement in reported understanding of the procedure, its risks and its benefits. The approach is not limited to cardiology and has the potential to be applied to all specialties in medicine.